2015
DOI: 10.1063/1.4922262
|View full text |Cite
|
Sign up to set email alerts
|

An accurate and efficient computational protocol for obtaining the complete basis set limits of the binding energies of water clusters at the MP2 and CCSD(T) levels of theory: Application to (H2O)m, m = 2-6, 8, 11, 16, and 17

Abstract: We report MP2 and Coupled Cluster Singles, Doubles, and perturbative Triples [CCSD(T)] binding energies with basis sets up to pentuple zeta quality for the (H2O)m=2-6,8 water clusters. Our best CCSD(T)/Complete Basis Set (CBS) estimates are -4.99 ± 0.04 kcal/mol (dimer), -15.8 ± 0.1 kcal/mol (trimer), -27.4 ± 0.1 kcal/mol (tetramer), -35.9 ± 0.3 kcal/mol (pentamer), -46.2 ± 0.3 kcal/mol (prism hexamer), -45.9 ± 0.3 kcal/mol (cage hexamer), -45.4 ± 0.3 kcal/mol (book hexamer), -44.3 ± 0.3 kcal/mol (ring hexamer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 93 publications
(199 reference statements)
8
80
0
Order By: Relevance
“…However, in some cases in the current studies, we noticed a reverse situation for the limiting value (the CBSextrapolated raw energy was less attractive than the CP corrected). A similar and unrealistic raw (− 4.95 kcal/mol) and CP-corrected energy (− 5.02 kcal/mol) ordering also reported Xantheas [42].…”
Section: Introductionsupporting
confidence: 53%
“…However, in some cases in the current studies, we noticed a reverse situation for the limiting value (the CBSextrapolated raw energy was less attractive than the CP corrected). A similar and unrealistic raw (− 4.95 kcal/mol) and CP-corrected energy (− 5.02 kcal/mol) ordering also reported Xantheas [42].…”
Section: Introductionsupporting
confidence: 53%
“…Their theoretical studies provide new insights into the mechanism of chiral recognition in small water clusters, especially for monocyclic water clusters, at the atomic level. Recently, an accurate and efficient computational protocol, i. e., second order approximation of Møller-Plesset perturbation theory (MP2) and Coupled Cluster Singles and Doubles (Triple) (CCSD(T)) based on perturbative method, for characterization of waters clusters is reviewed by Tschumper et al [21] and Xantheas et al [22] Some of these high-level studies showed the electronic structure of water clusters as large as (H 2 O) 17 . Accurate energetics of hydrogen bonds in water clusters are important not only for the development of interaction potentials for water, but also for assessing the accuracy of other theoretical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an accurate and efficient computational protocol, i. e., second order approximation of Møller–Plesset perturbation theory (MP2) and Coupled Cluster Singles and Doubles (Triple) (CCSD(T)) based on perturbative method, for characterization of waters clusters is reviewed by Tschumper et al . and Xantheas et al . Some of these high‐level studies showed the electronic structure of water clusters as large as (H 2 O) 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest energy isomers for n = 3 – 5 are cyclic, with monotonically increasing HB strengths. 18 Thus, one might expect the transition temperatures to increase monotonically with n . Figure 5 shows P ( r ) for these three clusters from which the onset of bifurcation, melting, and vaporization can be gleaned as upward deviating tails in comparison to the SND.…”
Section: Resultsmentioning
confidence: 99%